De novo mutations in the genome organizer CTCF cause intellectual disability - Gregor, Anne; Oti, Martin; Kouwenhoven, Evelyn N.; Hoyer, Juliane; Sticht, Heinrich; Ekici, Arif Bülent; Kjaergaard, Susanne; Rauch, Anita; Stunnenberg, Hendrik G.; Uebe, Steffen; Vasileiou, Georgia; Reis, André; et al. (American Journal of Human Genetics, 2013)
An increasing number of genes involved in chromatin structure and epigenetic regulation has been implicated in a variety of developmental disorders, often including intellectual disability. By trio exome sequencing and subsequent mutational screening we now identified two de novo frameshift mutations and one de novo missense mutation in CTCF in individuals with intellectual disability, microcephaly, and growth retardation. Furthermore, an individual with a larger deletion including CTCF was identified. CTCF (CCCTC-binding factor) is one of the most important chromatin organizers in vertebrates and is involved in various chromatin regulation processes such as higher order of chromatin organization, enhancer function, and maintenance of three-dimensional chromatin structure. Transcriptome analyses in all three individuals with point mutations revealed deregulation of genes involved in signal transduction and emphasized the role of CTCF in enhancer-driven expression of genes. Our findings indicate that haploinsufficiency of CTCF affects genomic interaction of enhancers and their regulated gene promoters that drive developmental processes and cognition.
EVALuna2:9184